Facile renewable synthesis of nitrogen/oxygen co-doped graphene-like carbon nanocages as general lithium-ion and potassium-ion batteries anode. (15th October 2020) - Sun, Yuanhe; Zhu, Daming; Liang, Zhaofeng; Zhao, Yuanxin; Tian, Weifeng; Ren, Xiaochuan; Wang, Juan; Li, Xiaoyan; Gao, Yi; Wen, Wen; Huang, Yaobo; Li, Xiaolong; et al.
Abstract: Environmentally-friendly carbon-based materials possess the potential applications as general anode for alkali-ion batteries. However, the existing carbon-based materials cannot satisfy the increasing demand for high energy density and need further active exploration. Herein, nitrogen/oxygen co-doped graphene-like carbon nanocages (NOGCN) is synthesized from biomass cytidine on hydro-soluble sodium chloride nanocrystals by a one-step method as a general lithium and potassium-ion batteries anode. All reactants are completely renewable and readily available. The nitrogen/oxygen-doping, large interlayer spacing and robust self-supporting nanocage architecture greatly favour electrolyte penetration and improve the kinetics for ion and electron transport, resulting in extraordinary electrochemical performance. The synthesized NOGCN electrodes exhibit a high lithiation storage capacity of 620 mA h g −1 over 500 cycles at 500 mA g −1, with continuously magnifying capacity. Moreover, the impressive reversible potassiation capacity (355 mA h g −1 at 200 mA g −1 ) and rate capability (114 mA h g −1 at 1000 mA g −1 ) were achieved despite the large-sized potassium ions. Kinetic analysis and density functional theory calculations elaborately illustrate the Li/K-absorption properties of the N/O-doped graphene-like structure, further demonstrating the chemical affinity and superiority in Li/K storage. This study provides a facile and completely renewable method to prepare promising general anode material for alkali-ion batteries. Graphical abstract: Image 1